Hydrogeological Study in and around Birendranagar Municipality, Surkhet Valley, Mid-Western Nepal - B. C., Roshani; Pathak, Dinesh; Gautam, Ramesh (Bulletin of the Department of Geology, 2020)
This study is carried out in parts of Surkhet valley, which is one of the Dun valleys (Inner Terai) in Nepal. Tubewell data was collected, dug well inventory with water table measurement was carried out followed by the data analysis leading to the groundwater resource assessment of the study area. The subsurface sediment distribution in the study area consist clay, sand and gravel giving rise to multiple aquifer horizons. Groundwater potential map has been prepared for parts of Surkhet valley and groundwater resource assessment has been carried out for the entire valley. Groundwater potential map was prepared using various thematic layers. Weights and rank were assigned, respectively to each thematic layer and its classes based on their significance for the groundwater occurrence. Most of the study area has medium groundwater potential with low potential at north east and high potential at southeast of the study area. The groundwater resource assessment for the valley, carried out by water balance method and aquifer analysis reveals that there is good groundwater reserve in the valley that can significantly fulfill the water demand in the area if properly exploited with required management of land and water resources in the area.